2011
DOI: 10.1587/transcom.e94.b.2454
|View full text |Cite
|
Sign up to set email alerts
|

CMOS Imaging Devices for Biomedical Applications

Abstract: SUMMARYWe review recently obtained results for CMOS (Complementary Metal Oxide Semiconductor) imaging devices used in biomedical applications. The topics include dish type image sensors, deep-brain implantation devices for small animals, and retinal prosthesis devices. Fundamental device structures and their characteristics are described, and the results of in vivo experiments are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, CMOS has the advantage of being a cost-effective commercial technology for production of large matrices. This makes SPADs manufactured in this technology ideal for different medical imaging applications [7]. In this work SPADs with multiplication layers buried at different depths have been studied with a focus on lower DCR and high PDE in the NIR region to target Diffusion Correlation Spectroscopy (DCS) applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CMOS has the advantage of being a cost-effective commercial technology for production of large matrices. This makes SPADs manufactured in this technology ideal for different medical imaging applications [7]. In this work SPADs with multiplication layers buried at different depths have been studied with a focus on lower DCR and high PDE in the NIR region to target Diffusion Correlation Spectroscopy (DCS) applications.…”
Section: Introductionmentioning
confidence: 99%
“…We propose to use complementary metal-oxide-semiconductor (CMOS) image sensors for bioimaging. [7][8][9][10][11][12][13] Such sensors are suitable for detecting fluorescent beads because they can measure fluorescence and have high-resolution imaging functions. By using such sensors, the system becomes simple and small.…”
Section: Introductionmentioning
confidence: 99%
“…Several instruments that photostimulate neurons in the brain with optogenetics have recently been developed 7 8 9 , in addition to several functional brain-imaging techniques 10 11 12 13 14 . Micro complementary-metal-oxide-semiconductor (CMOS) image sensors enable less invasive imaging in living tissue 15 16 17 18 19 20 21 . Previous studies have demonstrated that a fluorescence imaging system enables potentiometry in primary cultured neurons and in the brain with multiple sensors 22 23 24 25 .…”
mentioning
confidence: 99%